Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/agronomy12081779
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mapping and Identification of the Gibberellin 3-Oxidase Gene GA3ox Leading to a GA-Deficient Dwarf Phenotype in Pumpkin (Cucurbita moschata D.)

Abstract: Plant height is an important indicator in the ideal plant model and contributes to optimizing yield and lodging resistance. The emergence of a dwarfing phenotype provides an opportunity for plant height improvement. In a previous study, we identified a dwarf mutant Si1 in pumpkin (Cucurbita moschata D.) obtained by ethyl methane sulfonate (EMS) mutagenesis of the inbred line N87. Phenotype identification for Si1 revealed a decrease in cell size and shorter internodes than those of wild type. Genetic analysis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…wf was screened in the M2 generation population of the pumpkin mutant library that we had established earlier (Min et al, 2022). Throughout the entire flower development, wf had white‐flowered petals, which differed from the yellow‐flowered petals of wild‐type N87 plants (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…wf was screened in the M2 generation population of the pumpkin mutant library that we had established earlier (Min et al, 2022). Throughout the entire flower development, wf had white‐flowered petals, which differed from the yellow‐flowered petals of wild‐type N87 plants (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, a foundation is laid to better understand the regulatory mechanisms of flower‐colour formation in tree peony plants. Similarly, Min et al (2022) combined BSA‐Seq and RNA‐Seq analyses to investigate genes that control a dwarfing phenotype in pumpkin mutant, and CmoCh08G006170 is determined as the most likely candidate gene. In the present study, RNA‐Seq analysis showed that the DEGs were highly enriched in carotenoid biosynthesis and degradation pathways, and the expression of CmoCh14G005820 was downregulated in petals of wf .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations